Promoting equity in medical research: ensuring access to publishing opportunities for researchers in Syria and Palestine - Hamdah Hanifa; Alhareth M. Amro (BMC Medical Education, 2024)
Abstract In the face of ongoing conflicts and economic instability, researchers in low- and middle-income countries, particularly in regions like Syria and Palestine, grapple with significant financial barriers to publishing their work. These challenges not only hinder the dissemination of critical medical research but also impede the advancement of medical education. The exorbitant costs associated with publishing in prestigious journals, coupled with limited financial support, create an environment where groundbreaking research often remains inaccessible. This comment utilizes a review of the literature and researcher observations to explore the profound impact of these financial obstacles on the progress of medical research and education, advocating for more equitable publishing practices that support researchers in conflict-stricken regions.